Unequivocal interpretation of dobutamine stress echocardiography in low‐flow, low‐gradient aortic stenosis by right parasternal view. Issue 1 (18th December 2021) - Setti, Martina; Nistri, Stefano; Rossi, Andrea; Mantovani, Francesca; Ribichini, Flavio L.; Benfari, Giovanni
Abstract: We present the case of a 77‐years‐old man with aortic valve stenosis (AS) and reduced left ventricular ejection fraction, in whom right parasternal view provided the best hemodynamic evaluation of AS severity during dobutamine stress echocardiography